Cognition and reality : principles and implications of cognitive psychology - Neisser, Ulric (San Francisco : W. H. Freeman and Company, 1976)
Surveys contemporary theories of perception, criticizing mechanistic information-processing models and stressing differences between perception in the external world and in experimental laboratory situations
Chapter 1 Introduction, 2 - Theories of perception, 3 - Ordinary seeing, 4 - Schemata, 5 - Attention and the problem of capacity, 6 - Cognitive maps, 7 - Imagining and remembering, 8 - Perceiving and using speech, 9 - Some consequences of cognition
Includes bibliographical references and index
Keywords: Cognition